Environmental education as a tool for the implementation of selective collection door to door in community of Velho Timbo - Pacatuba (CE) - Guilherme, Camila Santos Lima Verde; Bastos, Ana Karine Pessoa (Revista Hipótese, 2017)
The objective of the study is to trace the profile of collectors of Pacatuba and implement selective collection door to door in the Velho Timbó community, in the municipality of Pacatuba. Through the application of a questionnaire were extracted from the collectors socioeconomic data, your work reality, as well as their perception about acting as environmental agents, it showed that many were aware of how much helped the environment.
Keywords: Recycling; Collectors of Recyclable Materials; Selective Collection; Environmental Education